Disruption within brain default mode network in postpartum women without depression. Issue 18 (May 2020) - Zheng, Jin-Xia; Ge, Lili; Chen, Huiyou; Yin, Xindao; Chen, Yu-Chen; Tang, Wen-Wei
Abstract : Abstract: Previous studies have demonstrated that cognitive dysfunction is associated with neurophysiological changes in postpartum period. This study aimed to investigate the intrinsic functional connectivity (FC) pattern within the default mode network (DMN) and its associations with cognitive dysfunction in postpartum women without depression revealed by resting-state functional magnetic resonance imaging (fMRI). Resting-state fMRI scans were acquired from 21 postpartum women and 21 age- and education-matched nulliparous women. The posterior cingulate cortex (PCC) was selected as the seed region to detect the FC patterns and then determine whether these changes were related to specific cognitive performance. Compared with the nulliparous women, postpartum women had a significantly decreased FC between the PCC and the left medial prefrontal cortex (mPFC). After correcting for age and education, the reduced FC between the PCC and the left mPFC was positively correlated with the poorer Clock-Drawing Test (CDT) scores in postpartum women ( r = 0.742, P < .001). The present study mainly demonstrated decreased resting-state FC pattern within the DMN regions that was linked with impaired cognitive function in postpartum women. These findings illustrated the potential role of the DMN in postpartum women that will provide novel insight into the underlying neuropathological mechanisms in postpartum period.